Effect of γ-irradiation and the use of combined treatments with edible bioactive coating on carrot preservation. (June 2021) - Ben-Fadhel, Yosra; Cingolani, Maria Celeste; Li, Leilei; Chazot, Guillaume; Salmieri, Stephane; Horak, Celina; Lacroix, Monique
Highlights: Gamma-irradiation of Ca-Cas improved the rheological properties of the coating. Cross-linked coating was applied to enhance the quality of pre-cut carrots. Bioactive coating combined with irradiation extended the shelf-life of carrots. Synergic activity was noted between active coating and irradiation post-treatment. Abstract: For increasing the shelf-life of carrot slices during storage, a bioactive edible coating was applied. An antimicrobial nanoemulsion (composed of citrus extract, cranberry juice and essential oils) was incorporated into a calcium caseinate (Ca-Cas)-based encapsulation matrix. Gamma-irradiation at 32 kGy was evaluated for its ability to improve the physicochemical properties of the coating via Ca-Cas cross-linking. Irradiation of Ca-Cas was found to be effective in preserving the mechanical properties of the coating containing the nanoemulsion. Pre-cut carrots were then subjected to different coatings applied alone or combined to gamma-irradiation post-treatment at 0.5 kGy. The quality and the shelf-life of carrot were assessed by evaluating the weight loss, texture and color of carrots as well as their microbial quality. The combined treatment of bioactive coating with irradiation showed a synergistic potential and a higher efficiency to extend the shelf-life of carrots and maintain their quality throughout storage, compared to single treatments.